Intercropping of tobacco and maize at seedling stage promotes crop growth through manipulating rhizosphere microenvironment - Ma, Junmei; Liu, Di; Zhao, Peiyan; Dou, Min; Yang, Xiuhua; Liu, Shulei; Nian, Fuzhao; Tong, Wenjie; Li, Junying; Xu, ZhaoLi; Zhang, Liuchen; Zhang, Hong; et al. (Frontiers in Plant Science, 2024)
Changes in the rhizosphere microbiome and metabolites resulting from crop intercropping can significantly enhance crop growth. While there has been an increasing number of studies on various crop combinations, research on the intercropping of tobacco and maize at seedling stage remains limited. This study is the first to explore rhizosphere effects of intercropping between tobacco and maize seedling stages, revealing important effects on soil microbial community composition and metabolite profiles, thereby regulating crop growth and improving soil balance. Compared with mono-cropping, intercropping increased the biomass of the two crops and promoted the nutrient absorption of nitrogen, phosphorus and potassium. Under intercropping conditions, the activities of sucrase, catalase and nitrate reductase in tobacco rhizosphere soil and the content of available potassium, the activities of nitrate reductase and acid phosphatase in maize rhizosphere soil were significantly increasing. Rhizosphere soil bacterial and fungal communities such as Sphingomonas, Massilia, Humicola and Penicillium respond differently to crop planting patterns, and soil dominant microbial communities are regulated by environmental factors such as pH, Organic Matter, Available Potassium, Nitrate Reductase, and Urease Enzyme. Network analysis showed that soil microbial communities were more complex after intercropping, and the reciprocal relationship between bacteria and fungi was enhanced. The difference of metabolites in soil between intercropping and monocropping system was mainly concentrated in galactose metabolism, starch and sucrose metabolism pathway, and the content of carbohydrate metabolites was significantly higher than that of monocropping soil. Key metabolites such as D-Sucrose, D-Fructose-6-Phosphate, D-Glucose-1-Phosphatel significantly influence the composition of dominant microbial communities such as Sphingomonas and Penicillium. This study explained the effects of intercropping between flue-cured tobacco and maize on the content of soil metabolites and soil microbial composition in rhizosphere soil, and deepened the understanding that intercropping system can improve the growth of flue-cured crops seedlings through rhizosphere effects.